Job Insecurity, Komitmen Organisasi Karyawan Dan Kepuasan Kerja Serta Dampaknya Terhadap Intention To Quit - Mawei, Ronald (JURNAL RISET BISNIS DAN MANAJEMEN, 2016)
Job dissatisfaction often culminates in a desire to get out of the business/intention to quit. Some ofthe effects of high level intention to quit (are) i.e. the productivity of employee is declining, thecompany's business activity is disrupted, moral issues arising out of the work of other employees, the cost of recruiting, interviewing, and the high level selection, the administration cost checking of processing new employees the allowance and the cost of lost opportunities because of new employees had to learn new skills. Based on the results of the research found that Job Insecurity influence significantly intention to quit on employees at PT. PLN Manado area. The commitment of the employees did not influence significantly on intention to quit on employees outsourcing at PT. Asia PLN Manado area. Job satisfaction influence significantly to the Intention to Quit on employees atPT. Asia PLN Manado area.Keywords: Job Insecurity, Employee Organizational Commitment, Job Satisfaction, Intention To Quit.